1998
DOI: 10.1046/j.1432-1327.1998.2510227.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of leukotriene‐C4 synthase in platelets and species distribution of the enzyme activity

Abstract: Human platelets have been demonstrated to possess leukotriene (LT)-C 4 synthase activity and may thus be involved in transcellular 5(S)-hydroxy-6(R)-S-glutathionyl-7,9-trans-11,14-cis-eicosatetraenoic acid (LTC 4 ) synthesis. In this study, platelets from seven different species were screened for LTC 4 synthase activity. Very high enzyme activity was observed in suspensions of bovine platelets, with approximately 70% conversion of 5(S)-trans-5,6-oxido-7,9-trans-11,14-cis-eicosatetraenoic acid (LTA 4 ) to LTC 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 4 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…(3) The possibility of LTB 4 and LTC 4 production by transcellular biosynthesis is also assumed [31][32][33]. That is, LTA 4 is released into the extracellular space along with LTB 4 , and LTA 4 is converted to LTC 4 by cells that express LTC 4 synthase, such as mast cells, eosinophils, platelets [34][35][36] and endothelial cells [37][38][39]. Nasser et al [40] reported that large numbers of eosinophils and mast cells are present in tissues obtained from AIA patients by bronchial biopsy compared with those in tissues obtained from ATA patients.…”
Section: Discussionmentioning
confidence: 99%
“…(3) The possibility of LTB 4 and LTC 4 production by transcellular biosynthesis is also assumed [31][32][33]. That is, LTA 4 is released into the extracellular space along with LTB 4 , and LTA 4 is converted to LTC 4 by cells that express LTC 4 synthase, such as mast cells, eosinophils, platelets [34][35][36] and endothelial cells [37][38][39]. Nasser et al [40] reported that large numbers of eosinophils and mast cells are present in tissues obtained from AIA patients by bronchial biopsy compared with those in tissues obtained from ATA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly this enzyme is also expressed in platelets, which do not contain 5-LO. (96,97) However, platelets can import LTA 4 generated in 5-LO containing cells to synthesize LTC 4 through a process termed transcellular metabolism (98). The actions of LTB 4 are mediated via at least two distinct G protein-coupled receptors, referred to as BLT 1 and BLT 2 .…”
Section: The Lipid Fraction Of Postshock Mesenteric Provokes Acute Lumentioning
confidence: 99%
“…Treatment of human platelets with helenalin (86) has been shown to cause irreversible inhibition of LTC 4 synthase in a concentration-and time-dependent manner, with an IC 50 of 12µM after a 60-min preincubation (Fig. 26) [39]. This effect was not related to decreased GSH levels or cytotoxicity.…”
Section: Helenalinsmentioning
confidence: 89%